2020
DOI: 10.1111/eci.13398
|View full text |Cite
|
Sign up to set email alerts
|

A novel way to quantify schizophrenia symptoms in clinical trials

Abstract: Background A major problem in quantifying symptoms of schizophrenia is establishing a reliable distinction between enduring and dynamic aspects of psychopathology. This is critical for accurate diagnosis, monitoring and evaluating treatment effects in both clinical practice and trials. Materials and methods We applied Generalizability Theory, a robust novel method to distinguish between dynamic and stable aspects of schizophrenia symptoms in the widely used Positive and Negative Symptom Scale (PANSS) using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…across cultures/countries). To date, G-Theory has been applied to establish reliability and generalizability of assessment scores across many different disciplines including medicine 21 , rehabilitation 22 , psychology 17 , psychiatry 23 and education 18 .…”
Section: Introductionmentioning
confidence: 99%
“…across cultures/countries). To date, G-Theory has been applied to establish reliability and generalizability of assessment scores across many different disciplines including medicine 21 , rehabilitation 22 , psychology 17 , psychiatry 23 and education 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several published clinical studies, including randomized double‐blind placebo‐controlled trials, showed some beneficial effects of NAC as an efficient therapy for schizophrenia (Table 3). NAC administration for a minimum of 4 weeks in doses ranging from 0.6 to 3.6 g day −1 to patients who underwent clinical antipsychotic therapy or without clinical therapy diminished negative symptoms (Berk, Copolov, Dean, Lu, Jeavons, Schapkaitz, Anderson‐Hunt, Judd, et al, 2008; Breier et al, 2018; Bulut et al, 2009; Di Rosa et al, 2010; Farokhnia et al, 2013; Lavoie et al, 2008; Medvedev et al, 2020; Rossell et al, 2016; Sepehrmanesh et al, 2018; Tharoor et al, 2018; Zhang et al, 2015). A few studies reported the effect of NAC on positive symptoms (Bulut et al, 2009; Di Rosa et al, 2010; Medvedev et al, 2020; Sepehrmanesh et al, 2018; Zhang et al, 2015), but the research data were weaker than those for negative symptoms.…”
Section: Nac In Psychiatric Disorders—clinical Studiesmentioning
confidence: 99%
“…NAC administration for a minimum of 4 weeks in doses ranging from 0.6 to 3.6 g day −1 to patients who underwent clinical antipsychotic therapy or without clinical therapy diminished negative symptoms (Berk, Copolov, Dean, Lu, Jeavons, Schapkaitz, Anderson‐Hunt, Judd, et al, 2008; Breier et al, 2018; Bulut et al, 2009; Di Rosa et al, 2010; Farokhnia et al, 2013; Lavoie et al, 2008; Medvedev et al, 2020; Rossell et al, 2016; Sepehrmanesh et al, 2018; Tharoor et al, 2018; Zhang et al, 2015). A few studies reported the effect of NAC on positive symptoms (Bulut et al, 2009; Di Rosa et al, 2010; Medvedev et al, 2020; Sepehrmanesh et al, 2018; Zhang et al, 2015), but the research data were weaker than those for negative symptoms. In addition, NAC improves cognitive symptoms, including working memory, mismatch negativity, and global functioning (Berk, Copolov, Dean, Lu, Jeavons, Schapkaitz, Anderson‐Hunt, Judd, et al, 2008; Carmeli et al, 2012; Conus et al, 2018; Di Rosa et al, 2010; Rapado‐Castro et al, 2017; Sepehrmanesh et al, 2018).…”
Section: Nac In Psychiatric Disorders—clinical Studiesmentioning
confidence: 99%
“…Shortened intervals can show respect for the potential challenges associated with a participant's diminished ability to concentrate (APA, 2013;Manojlovic & Nikolic-Popovic, 2016;Medvedev et al, 2021).…”
Section: S Hortened Interval S: Theore Ti C Al Foundationmentioning
confidence: 99%
“…Instead, they "must be recognized as valuable to society… and as distinct contributors to diversity of thought and experience" (Moore, 2020, p. 250). To facilitate OADWS' expression of their thoughts and ideas, given their unique needs related to potentially diminished concentration, research sessions can be broken up into shorter periods of time (Medvedev et al, 2021;Moore, 2020;Pawełczyk et al, 2018).…”
Section: S Hortened Interval S: Theore Ti C Al Foundationmentioning
confidence: 99%